Gauging the E-Readiness for the Integration of Information and Communication Technology Into Pre-Tertiary Education in Ghana: An Assessment of Teachers' Technological Pedagogical Content Knowledge (TPACK) - Gyamfi, Samuel Adu; Gyaase, Patrick Ohemeng; Kuranchie, Alfred (International journal of information and communication technology education, 2019)
Countries are investing in information and communication technology (ICT) infrastructure and educating their citizens for effective ICT utilization. The attainment of the anticipated benefits hinges on effective integration of ICT in various levels of education. Effective integration of ICT requires educators and teachers who possess the skills to harness the capabilities of ICT into their teaching and learning environments. This article assesses the extent of pre-university teachers' e-readiness to utilize ICT in teaching their various subjects by assessing their technological pedagogical content knowledge (TPACK). Although the ICT literacy of teachers in the pre-university schools in Ghana is high, their ability to utilize ICT to design and deliver subject contents and improve the learning environments of their respective subjects is low. The article suggests a comprehensive retooling of teachers with capabilities to integrate ICT in teaching their subjects.